Decadent Orientalisms : The Decay of Colonial Modernity - Fieni, David (Book collections on Project MUSE., 2020)
Decadent Orientalisms presents a sustained critique of the ways Orientalism and decadence have formed a joint discursive mode of the imperial imagination. Rather than attending to Orientalism as a repertoire of cliches and stereotypes, Fieni reads both Western and Islamic discourses of decadence to show the diffuse, yet coherent network of institutions that have constituted Orientalism's power.